A one-tube rapid visual CRISPR assay for the field detection of Japanese encephalitis virus - Xu, B.; Gong, P.; Zhang, Y.; Wang, Y.; Tao, D.; Fu, L.; Khazalwa, Emmanuel M.; Liu, H.; Zhao, S.; Zhang, X.; Xie, S. (Elsevier, 2022)
Early and rapid detection of Japanese encephalitis virus (JEV) is necessary for timely preventive and control measures. However, JEV RNA detection remains challenging due to the low level of viremia. In this study, a RApid VIsual CRISPR (RAVI-CRISPR) assay based on reverse transcription loop-mediated isothermal amplification (RT-LAMP) and CRISPR/Cas12a targeting was developed for easy detection of JEV in the field. We showed successful detection of 8.97 or more copies of the C gene sequence of JEV RNA within approximately 60 min. This assay also displayed no cross-reactivity with other porcine pathogens. We applied our one-tube RAVI-CRISPR assay to 18 brain tissue sample for JE diagnosis. The results from both fluorescence intensity measurements and directly naked-eye visualization were consistent with those from real-time PCR analysis. Taken together, our results showed that one-tube RAVI-CRISPR assay is robust, convenient, sensitive, specific, affordable, and potentially adaptable to on-site detection or surveillance of JEV in clinical and vector samples.